The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3390/nu6072552
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Choline on Hepatic Lipid Metabolism, Mitochondrial Function and Antioxidative Status in Human Hepatic C3A Cells Exposed to Excessive Energy Substrates

Abstract: Choline plays a lipotropic role in lipid metabolism as an essential nutrient. In this study, we investigated the effects of choline (5, 35 and 70 μM) on DNA methylation modifications, mRNA expression of the critical genes and their enzyme activities involved in hepatic lipid metabolism, mitochondrial membrane potential (Δψm) and glutathione peroxidase (GSH-Px) in C3A cells exposed to excessive energy substrates (lactate, 10 mM; octanoate, 2 mM and pyruvate, 1 mM; lactate, octanoate and pyruvate-supplemented me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 42 publications
5
48
0
1
Order By: Relevance
“…These results probably indicate that the enhanced lipogenesis was not associated with simultaneous increase in cholesterol metabolism for lipoprotein package and export out of the liver and consequently greater infiltration of triglyceride in the liver (Zhu et al . ). This action may relate to a pathophysiological situation induced by a higher concentration of insulin or, alternatively, may imply an insulin‐independent role for GLP‐1 in regulation of lipid metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…These results probably indicate that the enhanced lipogenesis was not associated with simultaneous increase in cholesterol metabolism for lipoprotein package and export out of the liver and consequently greater infiltration of triglyceride in the liver (Zhu et al . ). This action may relate to a pathophysiological situation induced by a higher concentration of insulin or, alternatively, may imply an insulin‐independent role for GLP‐1 in regulation of lipid metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that altering choline availability or hepatic choline metabolism drives patterns of altered lipid homeostasis (10,(28)(29)(30)(31)(32)(33)(34)(35). Early studies by Charles Best and others documented that liver dysfunction associated with choline deficiency was reversed by choline supplementation via delivery of PC (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…In direct opposition of NPC1L1, the ABCG5/ABCG8 heterodimer limits intestinal absorption and facilitates biliary secretion of cholesterol [2]. Mutations in SOD, GSH-Px, CAT Upregulation [50][51][52] VLDL metabolism MTP Upregulation [53] either ABCG5 or ABCG8 cause sitosterolemia. Treatment of Hep3B cells with pravastatin results in a significant increase in ABCG5 and ABCG8 levels, at least partially, by activating PPARα/liver X receptor α (LXRα) signaling pathway [25].…”
Section: Pparα Regulates Cholesterol Homeostasismentioning
confidence: 99%
“…It was reported that PPARα activation suppresses the expression of nicotinamide dinucleotide phosphate oxidase 4 (NOX4) and then attenuates superoxide production in the rat aorta [49]. On the other hand, treatment with PPARα ligands elevates the activities of endogenous antioxidase including superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) to remove free radicals [50][51][52]. Thus, a decrease in NOX4 expression as well as an increase in SOD, GSH-Px, and CAT activities may lead to reduced ox-LDL generation.…”
Section: Pparα Regulates Ldl Metabolismmentioning
confidence: 99%